1996
DOI: 10.1016/s0022-5347(01)65412-0
|View full text |Cite
|
Sign up to set email alerts
|

Modified Pubovaginal Sling for Treatment of Intrinsic Sphincteric Deficiency

Abstract: Our study confirmed the success of the modified pubovaginal fascial sling for treatment of intrinsic sphincteric deficiency. We were unable to obtain useful preoperative information from fluoro-urodynamic studies to predict which patients would experience failure to return to normal voiding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 15 publications
0
5
1
Order By: Relevance
“…Our results are disappointing compared with other studies that have reported ‘cure’ of stress incontinence in over 90% of women using sling procedures 6,9,31,33–45 . However, all these studies report on both shorter follow up and use non‐validated methods of assessing subjective improvement.…”
Section: Discussioncontrasting
confidence: 81%
See 2 more Smart Citations
“…Our results are disappointing compared with other studies that have reported ‘cure’ of stress incontinence in over 90% of women using sling procedures 6,9,31,33–45 . However, all these studies report on both shorter follow up and use non‐validated methods of assessing subjective improvement.…”
Section: Discussioncontrasting
confidence: 81%
“…However, all these studies report on both shorter follow up and use non‐validated methods of assessing subjective improvement. For a number of these authors women are considered cured even if they suffer continuing incontinence, as long as that incontinence is due to detrusor instability 6,36–39 . In our study urgency was strongly associated with failure of the operation.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…Sling insertion utilising a combined vaginal and abdominal approach, a vaginal approach alone or a suprapubic technique alone, with blind dissection beneath the urethra and bladder base, have all been described. The use of an abdominal approach alone is claimed to reduce bacterial contamination of the sling although the incidence of bladder and urethral injury may be slightly higher 12 . However, there is no definitive evidence to indicate which surgical approach is superior and this appears to be related to the preference and experience of the surgeon; it is the choice of material and tension which appear to most influence the outcome of sling surgery.…”
Section: The History Of Suburethral Sling Proceduresmentioning
confidence: 99%
“…However, successful surgery for stress incontinence has an effect on urge incontinence symptoms and on detrusor instability identified with CMG. Most reports show a 50-75% resolution rate of detrusor instability and urinary incontinence symptoms after successful surgery for stress incontinence [40][41][42][43][44][45]. Cucchi [33] found a relationship between stress incontinence and detrusor instability in some patients, which he suggested was causal.…”
Section: Stress Incontinence and Urge Incontinencementioning
confidence: 99%